2020
DOI: 10.1002/wer.1377
|View full text |Cite
|
Sign up to set email alerts
|

Application of diatomite for sorption of Pb, Cu, Cd and Zn from aqueous solutions: kinetic, thermodynamic studies and application of response surface methodology (RSM)

Abstract: Contamination of water and soil with toxic metals is a serious environmental issue. To study the Pb, Cu, Cd, and Zn sorption behavior by diatomite, batch experiments were carried out with increasing levels of initial concentration (0–200 mg/L) under different contact times (0–360 min) and temperatures (283, 293, 303, and 313 K). The effects of concentration (0–200 mg/L), pH (3–6), and ionic strength (0.01–0.06 mol/L) on the sorption were modeled using response surface methodology (RSM). Results showed that ads… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…It can carry out single-molecule adsorption and multimolecular layer adsorption as well . Diatomite can be widely used in metal ion adsorption and dye adsorption and can also function as a carrier for high content powder, especially suitable for processing liquid pesticides into a carrier of high content powder. Therefore, diatomite as a carrier of pesticides has high research value.…”
Section: Introductionmentioning
confidence: 99%
“…It can carry out single-molecule adsorption and multimolecular layer adsorption as well . Diatomite can be widely used in metal ion adsorption and dye adsorption and can also function as a carrier for high content powder, especially suitable for processing liquid pesticides into a carrier of high content powder. Therefore, diatomite as a carrier of pesticides has high research value.…”
Section: Introductionmentioning
confidence: 99%
“…Piri et al reported that diatomite could adsorb Cd, Cu and Pb successfully. 11 Pu et al found the adsorption capacity of NaP zeolite for Cu(II) in solution was 62.3 mg g À1 . 12 Adsorbents, especially prepared from renewable sources, brought about the widespread attention in wastewater treatment recent years.…”
Section: Introductionmentioning
confidence: 99%
“…The surface of CB has an irregular pore structure but a rough surface; while for BC and RHB, they have relatively few pores, showing the presence of dispersed particulate matter as well as a plate-like structure. The granular material on their surface could be crystals formed by some mineral elements ( Piri et al, 2020 ). Overall, DA has a relatively well-developed pore structure and a high specific surface area for better absorption.…”
Section: Resultsmentioning
confidence: 99%